Loss of UBE3A impacts both neuronal and non-neuronal cells in human cerebral organoids - R. Chris Estridge; Z. Begum Yagci; Dilara Sen; Tyler J. Johnson; Gautami R. Kelkar; Travis S. Ptacek; Jeremy M. Simon; Albert J. Keung (Communications Biology)
Abstract Angelman syndrome is a neurodevelopmental disorder caused by (epi)genetic lesions of maternal UBE3A. Research has focused largely on the role of UBE3A in neurons due to its imprinting in that cell type. Yet, evidence suggests there may be broader neurodevelopmental impacts of UBE3A dysregulation. Human cerebral organoids might reveal these understudied aspects of UBE3A as they recapitulate diverse cell types of the developing human brain. In this study, scRNAseq on organoids reveals the effects of UBE3A disruption on cell type-specific compositions and transcriptomic alterations. In the absence of UBE3A, progenitor proliferation and structures are disrupted while organoid composition shifts away from proliferative cell types. We observe impacts on non-neuronal cells, including choroid plexus enrichment. Furthermore, EMX1+ cortical progenitors are negatively impacted; potentially disrupting corticogenesis and delaying excitatory neuron maturation. This work reveals impacts of UBE3A on understudied cell types and related neurodevelopmental processes and elucidates potential therapeutic targets.